(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The monuments of Karakalpakstan that have survived to this day are authentic works of art that have entered the Treasury of world culture. They have been studied for many years by historians, archaeologists, architects, art historians, ethnographers and other specialists.